Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(y–3)^2 = y^2 –9 ????????????????????????????????????

(y–3)^2 = y^2 –9 ????????????????????????????????????

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5818 Points
2 months ago
Dear Student

LHS = (y–3)^2, which is similar to (a–b)^2identity, where (a–b)^2= a^2+b^2-2ab.
(y–3)^2= y^2+(3)^2–2y×3 = y^2+9–6y ≠y^2–9 = RHS
The correct statement is (y–3)^2= y^2+ 9–6y

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free